The Role of Small businesses in Achieving Economic Development in Palestine - Abu-Daoud, Asmaa Mahmoud; Iriqat, Ismail Salama (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aimed at identifying the reality of small businesses in the Palestinian society, and determining the extent to which these projects contribute to reducing unemployment and poverty and improving the standards of living of individuals. It also aimed at recognizing the extent to which the authorities in Palestine contribute to financially support those businesses. Method: To achieve its objectives, the study followed the analytical descriptive approach by conducting 7 interviews with relevant stakeholders and specialists in the field of supporting small businesses in addition to distributing 106 questionnaires to owners of small businesses. The study also used the content analysis method. Results: The study results showed that small projects contributed to combatting unemployment by providing alternatives to governmental and private jobs. The results of the study also showed that the government agencies attempt to coordinate with civil society institutions and the private sector in order to ensure compatibility and integration in the activities and programs that are offered to small businesses. Conclusion: This study paves the way for future research aimed at studying the issue of economic development. Results indicated that comprehensive development policies should take into account the local capabilities and the actual needs of the Palestinian society to determine the nature of the opportunities available to entrepreneurs and owners of small businesses.